Disseminated Intravascular Coagulation with Acutely-Thrombosed Popliteal Aneurysm - Ichibori, Yasuhiro (The Editorial Committee of Annals of Vascular Diseases, 2010)
Disseminated intravascular coagulation (DIC) is an extremely rare complication of acute thrombosis in popliteal aneurysms and makes it difficult to restore the blood flow with thrombolytic therapy or surgical repair. A 75-year-old man with a history of hypertension presented to the emergency department with complaints of right leg pain and bleeding tendency over a 5-day period. The laboratory findings and multislice computed tomography were suggestive of overt DIC caused by acute thrombosis in the right popliteal aneurysm. Successfully treated with medication, he could discharge without surgical or thrombolytic recanalization of the aneurysm.